Geoeconomic Aspects of the Change in the Bulgarian Regional Development After Covid-19 - Petrov, Kamen (Research Papers, 2023)
This article is dedicated to the emerging new challenges posed by the information revolution and intensive geoeconomic processes. The aim of the article is to bring out new moments and trends of interaction between geoeconomics and e-government. The article makes the chronology of the processes and phenomena that contribute to the development of geoeconomics and e-government. The methodology used in defining the problems is based on the reference of the expert assessment of leading analysts, the use of the network approach and the comparative analysis. For the first time in scientific thought the concept of geoelectronic control was introduced. This practice is a new attempt to analyze the new geoeconomic processes taking place in the XXI century. To a large extent, the processes of globalization and the opening of the world are accompanied by processes of defragmentation or regionalization. In this peculiar dichotomous model of development through e-government there is a mechanism for the implementation of effective socio-economic relations. This creates conditions for creating new types of relationships that identify the need to optimize issues related to the electronic environment, and hence the creation of new ethics and behavior of people as users of the information environment. As a result of this study, we can conclude that for the first time we assume that the global geoeconomics not only has spatial and territorial manifestations, but also imposes a new stereotype of the electronic environment.
Keywords: Geo-economics; Development; Region; Areal; Management; Strategy; Information